Experimental assessment of the pyramidal energy on water. - Pedro Díaz Rebollido; Luis Carlos Silva Ayçaguer; Mikhail Benet Rodríguez (Medisur)
Background and objectives: The debate around the so called ¨pyramidal energy¨ among those that accept their multiple uses and those that reject them has been present both in the scientific community and the population. A recent research has suggested changes in the conductivity and the pH of the water, exposed to the pyramidal effect. The need to asses such a claim is the reason for the present study. Method: The study was developed in the laboratory of Physiology of the Faculty of Medical Sciences of Cienfuegos. We worked with 30 test tube numbered consecutively, stuffed with 500 ml of water. It was measured the electric conductivity and the pH of the wa-ter in each one of them. Later on, half of them, chosen at random, were placed during four hours under a pyramid, and the remaining ones were located outside of the pyramid. The electric conductivity and the pH were determined by means of the potenciometric method The pyramid employed was built with solid bars of aluminum, of skeletal structure; their dimensions were those established by specialists. It was placed so that two sides of its base were parallel to the North-South axis magnetic of the Earth. The measures were carried out in a blind way by one of the ours under the supervision of the other two co authors. Confidence intervals of the mean differences were computed under both experimental conditions and for the two considered variables. Complementarily, the stockings were compared by means of the Student t test. Results and Conclusions: The average (DS) of the conductivity in the exposed test tubes to the pyramid before the exposition was 3,20 (0,07) and after 3,20 (0,05) (p=0,622); in the non exposed test tubes it was 3,18 (0,07) and 3,17 (0.06), (p=0.928). On the other hand, the average (DS) values of the pH in the test tubes exposed to the pyramid before the exposition was 8,08 (0,78) and after 8.42 (0.13) (p=0.605), and in the non exposed test tubes 8,32 (0,89) and 8,44 (0,08), (p=0,127). The effect of the pyramids didn't modify the conductivity neither the pH of the molecule of water. Our results suggest that pyramids do not produce any effect on water in relation with the two parameters studied. Any replications of an experience like ours -exactly the same or changing some para-meters as the duration of the exposition- will be welcome.